2018
DOI: 10.1002/sctm.17-0182
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Human Placental-Derived Stem Cells in Collagen VII Knockout (Recessive Dystrophic Epidermolysis Bullosa) Animal Model

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a devastating inherited skin blistering disease caused by mutations in the COL7A1 gene that encodes type VII collagen (C7), a major structural component of anchoring fibrils at the dermal‐epidermal junction (DEJ). We recently demonstrated that human cord blood‐derived unrestricted somatic stem cells promote wound healing and ameliorate the blistering phenotype in a RDEB (col7a1 −/−) mouse model. Here, we demonstrate significant therapeutic effect of a furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We recently showed that repeated injection of dextran/human serum albumin (D/HSA) buffer were able to extend the survival of some col7a1 −/− mice, most likely by adjusting fluid balance, although it had no significant effect on the median life span . The mice that survived enabled the current investigation on the dynamic development of TGFβ signaling in this animal model.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that repeated injection of dextran/human serum albumin (D/HSA) buffer were able to extend the survival of some col7a1 −/− mice, most likely by adjusting fluid balance, although it had no significant effect on the median life span . The mice that survived enabled the current investigation on the dynamic development of TGFβ signaling in this animal model.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Celgene Cellular Therapeutics, Inc. manufactured human placental-derived stem cells (HPDSCs) from full-term donor placentas following saline perfusion, red blood cell depletion, and volume reduction. The overall cell types as determined by flow cytometry analysis are similar between HPDSCs and CB [127]. However, HPDSCs contain a significantly higher level of both hematopoietic and non-hematopoietic stem and progenitor cells than CB.…”
Section: Human Umbilical Cord Blood and Placental Stem Cellsmentioning
confidence: 85%
“…A pilot clinical study demonstrated that adding HPDSCs as universal donor cells with CB transplantation in patients with malignant and nonmalignant diseases had no adverse effects and may reduce the incidence of aGvHD [128]. Administration of HPDSCs in a mouse model of RDEB, in the absence of any conditioning regimen, also resulted in significant improvement on the survival and disease manifestation of the recipient mice [127]. [125].…”
Section: Human Umbilical Cord Blood and Placental Stem Cellsmentioning
confidence: 99%
“…21 In a subsequent STEM CELLS Translational Medicine article, Liao et al explored the potential direct regenerative properties of HPDSCs by evaluating their efficacy in a mouse model of RDEB. 12 The authors demonstrated that a single intrahepatic administration of HPDSCs in the absence of any preconditioning or immunosuppression significantly increased the median life span of RDEB model mice (from 2 to 7 days) and alleviated hemorrhagic blistering. Encouragingly, an additional HPDSC administration further extended the median life span to 18 days.…”
Section: Related Articles Optimizing Cell Isolation and Surgical Manipulation To Support Subretinal Treatment Strategies For Retinal Degementioning
confidence: 98%